Identification of Risk Factors for Mortality Due to Multidrug-Resistant Tuberculosis Among Patients Managed at the Lufungula Tuberculosis Screening and Treatment Center in the National Police Health Zone, Kinshasa Provincial Health Division: A Survival Analysis. - Jacques; Gerard; Bob Senker Ndimba; Emmanuel; Zebe Mbadu; Jean-Paul; Jules (Student's Journal of Health Research Africa, 2026)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) is a major public health problem, particularly in sub-Saharan Africa. The Democratic Republic of Congo (DRC) is among the countries with a high burden of tuberculosis and multidrug-resistant tuberculosis. Identifying factors associated with mortality is essential to improving patient management and survival. This study aimed to identify risk factors for mortality among patients with MDR-TB followed at the Lufungula Tuberculosis Screening and Treatment Health Center, in the National Police Health Zone, Kinshasa. Methods: A retrospective study was conducted using data from 404 patients aged 20 to 54 years, registered between 2010 and 2019. Exhaustive sampling was used. Data were analyzed using SPSS version 25, R, and Stata 12. Survival analysis was performed using the Kaplan-Meier and Cox methods to identify factors associated with mortality. Results: Mortality was significantly higher among patients aged 20–29 years (p